2004
DOI: 10.1186/2046-0481-57-2-103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs, diagnosis and treatment of three dogs with angiostrongylosis in Ireland

Abstract: Infection with Angiostrongylus vasorum was diagnosed at necropsy on a dog that died from acute pulmonary haemorrhage, and on recovery of L1 larvae by Baermann examination of faeces from two dogs, one of which had abdominal pain and retroperitoneal haemorrhage, while the other had right-sided heart failure due to cor pulmonale. The presenting signs included syncope (one dog), exercise intolerance (two dogs), cough (two dogs), abdominal pain (one dog) and depression (one dog). One-stage prothrombin time and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
1
27
0
1
Order By: Relevance
“…The pre-patent period of 51 days confirms reports in the literature of a variation of the pre-patent period between 28 and 108 days after infection (Oliveira-Júnior et al, 2006;Mozzer et al, 2011). The use of fenbendazole was an effective therapeutic approach for the treatment of the dog, as observed in other studies of dogs infected with A. vasorum and treated with the same active ingredient (Martin et al, 1993;Brennan et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…The pre-patent period of 51 days confirms reports in the literature of a variation of the pre-patent period between 28 and 108 days after infection (Oliveira-Júnior et al, 2006;Mozzer et al, 2011). The use of fenbendazole was an effective therapeutic approach for the treatment of the dog, as observed in other studies of dogs infected with A. vasorum and treated with the same active ingredient (Martin et al, 1993;Brennan et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…The ensuing verminous pneumonia results in signs of chronic cough, dyspnea, exercise intolerance, anorexia, gagging, and weight loss. Vascular lesions due to the presence of adult worms include thromboarteritis and intimal proliferation, which can result in pulmonary hypertension and finally right congestive heart failure, adding syncope and ascites to the above list of signs (Bourque et al, 2008;Brennan et al, 2004;Koch and Willesen, 2009;Nicolle et al, 2006). Hemorrhagic diathesis due to coagulopathies of unknown etiology have been frequently associated with angiostrongylosis in both naturally and experimentally infected dogs Cury et al, 2002;Dodd, 1973;Ramsey et al, 1996;Sasanelli et al, 2008;Schelling et al, 1986).…”
Section: Clinical Diseasementioning
confidence: 94%
“…Since its discovery in France in 1866 by Baillet (Rosen and others 1970), A vasorum has been reported in dogs in Europe (Denmark, France, Germany, Ireland, Italy, Spain, Sweden, Switzerland, Turkey and the UK), Africa (Uganda), South America (Brazil and Columbia) and Canada (Newfoundland) (Brennan and others 2004, Bourque and others 2008, Traversa and Guglielmini 2008). It is widely assumed that foxes act as a reservoir of infection for dogs and a recent study has shown that infection is endemic in foxes in areas of the UK where there is a high incidence of A vasorum infection in canines (Morgan and others 2008).…”
mentioning
confidence: 99%
“…Dogs with cardiorespiratory signs present with a history that may include chronic coughing, exercise intolerance, syncope, dyspnoea and tachypnoea (Bolt and others 1994), whereas the coagulopathies can result in anaemia, subcutaneous haematomas, internal haemorrhages and prolonged bleeding from wounds or after surgery (Ramsey and others 1996, Brennan and others 2004, Morgan and others 2005). In neurological cases, paresis, depression, seizures, spinal pain, behavioural changes, ataxia and loss of vision have been described as potential results of aberrant nematode migration or subdural haemorrhage (Patteson and others 1993).…”
mentioning
confidence: 99%